Catalyst Asia Issue 04 - Institute for Societal Leadership, (Institutional Knowledge at Singapore Management University, 2016)
STORIES FROM THE GROUND Toiling Away on Land Issues Leading the Blind A Leading Secret The Road Less Travelled Migrant Rights' Fighter Power of Youth A Ground-up Initiative Picking Up The Pieces A Friend to Farmers Four Dollars, Well Spent Bottom-Up Revolution IN THE HOT SEAT The Heart of an Uncommon Leader Help For The Exploited When Social Revolutions Begin with #Hashtags Lending His Magical Touch Fighting Malaria PERSPECTIVES FROM THE TOP Steward Leadership Understanding Societal Leadership Reflections from A Work Stint with a Difference